G403(P) Tablet preferences in children and young people. (7th April 2014) - Batchelor, HK; Marriott, JF; Venables, RH; Stirling, HF; Callens, C; Hughes, K; Miller, C
Abstract : Aims: The aim was to determine the optimum size, shape and colour intensity of tablets for children and young people using both images and physical models. Materials and methods: This study used photo-realistic life-size 2D images (5 to 20 mm in length) and their corresponding identical physical 3D tablet models to assess the acceptability of tablet size. Exact replicas of tablets ranging in girth from caplet to oval to diamond shaped units were manufactured. These models were coated with three coloured coatings; white, pale lilac and dark purple. The images and models were the basis of a questionnaire administered to children and young people in schools, hospitals and at community events. Results: 183 individuals participated in the study; 74 children 6–7 years; 40 children 8–10 years; 40 young people 14–18 years and 29 adults. Most participants accepted a larger tablet size when looking at models compared to images. The largest tablet was the least acceptable as both an image and a physical model (<35 and <50% in all children and young people respectively). The 5 mm tablet gave unusual results as it was less popular than the next largest size in participants over the age of 8 years. In all populations the results showed that the caplet was the most popular shape followed by the oval and then the diamond as shown in Figure 1 . The shape preference was most pronounced in the younger populations; where differences of over 20% were observed in acceptance of the caplet tablet compared to the diamond. In the majority of cases the pale tablet was preferred to the dark tablet. This may be associated with familiarity with pale tablets and therefore they are more acceptable. Within this study all participants were presented tablets in 3 different shades; white, pale and intense purple; in children the white tablets were preferred over either coloured tablet. Conclusions: The design of tablets for paediatric populations should aim for a small caplet or other narrow girth shaped tablet that is white or pale to maximise acceptability in children.